The Thaha Movement and Social Transformation in Nepal: Insights from Rupchandra Bista’s Philosophy of Social Justice - Karki, Sano Bhai (Journal of Advanced Academic Research, 2026)
The seeking of social justice in Nepal is still being defined by age-old caste stratifications, pessimistic views of the world, and cultural regulations, which inhibit civic agency. In the same landscape, the Thaha Movement based on the philosophy of thaha or critical knowing by Rupchandra Bista, presents a valuable framework that would put forward a challenge on the epistemic principles of inequality. This work is going to explore the ideas of awareness, anti-fatalism, and rational discipline by Bista as the prism through which the concept of social justice in Nepal can be seen and how the Thaha Movement is related to the larger processes of social change. A conceptual review based on PRISMA with systematic search, screening and thematic synthesis of 21 relevant articles was undertaken based on their retrieval in academic databases and registers. The results show that the critical awareness importance placed on by Bista is an emancipatory instrument that helps individuals and communities to challenge the oppressive social systems. His fatality criticism is also an interruption of cultural discourse to justify inequality and clear conceptual space of agency and group empowerment. Moreover, the rational discipline he advocates connects the individual sense of ethical responsibility to systemic justice, which can make contributions to ethical governance and democracy. Generally speaking, the review presents the contemporary usefulness of the philosophy developed by Bista and emphasizes the prospects of the application of the Thaha Movement to shape more participatory, fair, and critically based methods of effecting change in Nepal.